Sistem Reservasi Jadwal Jasa Medis Fasilitas Kesehatan Kelas Satu Menggunakan QR Code Berbasis Android - Mohammad Hafiz Hersyah; Ririn Putri Anedya (Universitas Andalas, 2020)
This research aims to establish a reservation system or reservation schedule for health services in the health facility class one. This system uses qr code technology to identify health service schedule orders made by users. This system consists of a laptop webcam that functions as a device for reading data in QR codes, Arduino Uno microcontroller as a data processor for reading QR code results, an MP3 player module as a device for storing sound output, speakers functioning as sound output devices for reading QR codes and Android application as a system interface for ordering health service schedules in health facility class one and accessing databases. Ordering a health service schedule starts with the selection of the service schedule by the user on the android application, then the user will get a qr code as proof of the order made to identify the sequence that will later be read by the webcam laptop and the results processed by Arduino followed by the voice output from the speaker. This study shows the success rate of the system in making online schedule bookings by 100%. In the process of identifying the QR code using a webcam with bright lighting conditions it has a 100% success rate and with a reading range of 11-20 cm a 90% success rate is obtained. In testing, the sound output from the speakers obtained a success rate of 100%.